Soybean for good health and nutritional security - Talukdar, Akshay; Kumar, Ashish (Indian Farming, 2018)
Soybean is the richest source of effective plant proteins which can be a powerful alternative to the pulses to address the menace of protein and energy malnutrition prevalent in our country. Of late, soybean genotypes free from Kunitz trypsin inhibitor (KTI) and lipoxygenase have been developed at the Indian Institute of Soybean Research, Indore. Further, the taste and aroma of the beans should be as per liking of the Indian consumers so that it can reach more households as a popular functional food. Government intervention will be needed to harvest the benefits of soybean and transfer it to the needy consumers. To reach the poor and disadvantaged category of consumers, soybean can be distributed through public distribution system (PDS), mid-day meal and similar other government programmes. Such initiative would not only make soybean a household food but also ensure nutritional security to the consumer, and thus would help realize the current Government’s dream of ‘swastha bharat’ (Healthy India).